Effect of pulse flour storage on flour and bread baking properties. (March 2020) - Sopiwnyk, E.; Young, G.; Frohlich, P.; Borsuk, Y.; Lagassé, S.; Boyd, L.; Bourré, L.; Sarkar, A.; Dyck, A.; Malcolmson, L.
Abstract: The effect of storage on flour and baking properties of pulse flours was investigated. Commercially milled whole (yellow pea, navy bean, and chickpea) and dehulled/decorticated (yellow pea, red lentil) flours were stored in a warehouse, heated in the winter months. Flours were evaluated at 1, 2, 3, 6, 9, 12, 18, 24 months for water absorption capacity (WAC), colour, pasting properties, and lipoxygenase (LOX) activity. Stored pulse flours were combined with wheat flour (stored at −18 °C) as a 20% pulse/80% wheat flour blend, baked into bread and assessed for quality. Flour and baking properties of the pulse flours were not greatly affected with storage but whole flours showed greater changes than dehulled/decorticated flours. The greatest changes were found for flour colour (decreased L*) and bread crumb colour (increased a*). Bread flavour (increased bitterness/aftertaste/pulse flavour) and appearance (lower acceptability) were affected for most pulse flours with storage. The freshly milled flours had the highest LOX activity which decreased significantly by 1 month of flour storage. WAC was higher in the stored flours except for chickpea flour. Pasting properties, bread volume, and C-Cell properties were not consistently altered with flour storage but crumb firmness increased with storage for some flours. Highlights: Effect of pulse flour storage on flour and baking properties determined. Lipoxygenase activity highest in freshly milled flours. Storage affected flour colour (decreased L*) and WAC (tended to increase). Storage affected crumb colour (increased a*) but not volume or crumb structure. Whole flours more affected by storage than dehulled (decorticated) flours.